Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1007/bf01234122
|View full text |Cite
|
Sign up to set email alerts
|

Topographic mapping of human motor cortex with transcranial magnetic stimulation: Homunculus revisited

Abstract: The purpose of this study was to non-invasively evaluate the homuncular organization of the motor cortex in man. We used transcranial magnetic stimulation to induce motor evoked potentials (MEP's) in Abductor Pollicis Brevis (APB) and Biceps Brachii (BB) muscles of 10 healthy volunteers. The practicality and accuracy of magnetic stimulation to scalp sites one cm apart was increased by the application to the scalp of a flexible nylon grid with grid size of 1x1 cm. Responsive scalp sites collectively contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Additional evidence of recovery was obtained by the TMS study. An MEP with a level of latency compatible with the CST was evoked from the affected hand when stimulating the optimal scalp site of the affected hemisphere [2,13,20]. In the current patient, the above evidence suggests that some portion of the infarcted brainstem other than the CST was responsible for the recovery of motor function, and the main motor function of the affected hand seemed to be controlled by this posterior pathway, which had characteristics similar to those of the CST.…”
Section: Discussionsupporting
confidence: 52%
“…Additional evidence of recovery was obtained by the TMS study. An MEP with a level of latency compatible with the CST was evoked from the affected hand when stimulating the optimal scalp site of the affected hemisphere [2,13,20]. In the current patient, the above evidence suggests that some portion of the infarcted brainstem other than the CST was responsible for the recovery of motor function, and the main motor function of the affected hand seemed to be controlled by this posterior pathway, which had characteristics similar to those of the CST.…”
Section: Discussionsupporting
confidence: 52%
“…We assume, however, that the distortion, which occurs certainly when a 3D map is represented on a 2D coordinate system, is tolerable in the case of the motor cortex. Previous mapping experiments showed that cortical motor representation can be investigated despite the use of a 2D coordinate system [Boroojerdi et al, 1999;Cohen et al, 1991;Foltys et al, 2000;Macdonell et al, 1999;Metman et al, 1993;Wilson et al, 1993]. Furthermore, this technical restriction did not obviously affect the measure of MEP amplitudes, which was highly negatively correlated with the measure of spatial distances.…”
Section: Limitations Of the Studymentioning
confidence: 93%
“…The site of stimulation is less well localized compared with an electrode applied directly to the surface of the brain, so that the effective area of stimulation is larger than that obtained in acute experiments on anaesthetized subjects or animals. However, the centre of the most effective site for stimulation is very similar to that seen during neurosurgery, being slightly anterior to the best points for obtaining responses in muscles of the hand or arm [30,31]. One important difference between the techniques is that, in previous work, the brain has been stimulated with a train of several hundred stimuli at a rate of 50-60 Hz.…”
Section: Organization Of Human Swallowing Motor Cortexmentioning
confidence: 95%